2021
DOI: 10.1182/bloodadvances.2020002578
|View full text |Cite
|
Sign up to set email alerts
|

The fatty acid elongase ELOVL6 regulates bortezomib resistance in multiple myeloma

Abstract: Resistance to the proteasome inhibitor bortezomib (BTZ) represents a major obstacle in the treatment of multiple myeloma (MM). The contribution of lipid metabolism in the resistance of MM cells to BTZ is mostly unknown. Here we report that levels of fatty acid elongase 6 (ELOVL6) were lower in MM cells from BTZ-nonresponsive vs BTZ-responsive patients and in cultured MM cells selected for BTZ resistance compared with parental counterparts. Accordingly, depletion of ELOVL6 in parental MM cells suppressed BTZ-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…Thus, our study represents a novel approach to reducing MYC by targeting the FABP family. This work also builds upon data that myeloma cells exhibit aberrant amino acid, lipid, and energy metabolism [44], and data revealing the importance of metabolic enzymes in myeloma tumorigenesis [45] and drug resistance [46] by demonstrating the role of FABPs in MM cell metabolism and mitochondrial integrity. In sum, we identified a new protein family for therapeutic targeting in myeloma, and demonstrated, for the first time, the great potential for inhibiting it in MM.…”
Section: Discussionmentioning
confidence: 94%
“…Thus, our study represents a novel approach to reducing MYC by targeting the FABP family. This work also builds upon data that myeloma cells exhibit aberrant amino acid, lipid, and energy metabolism [44], and data revealing the importance of metabolic enzymes in myeloma tumorigenesis [45] and drug resistance [46] by demonstrating the role of FABPs in MM cell metabolism and mitochondrial integrity. In sum, we identified a new protein family for therapeutic targeting in myeloma, and demonstrated, for the first time, the great potential for inhibiting it in MM.…”
Section: Discussionmentioning
confidence: 94%
“…As the use of an ACSS2 inhibitor reduced myeloma growth both in vitro and in a diet-induced obese mouse model, the critical role of ACSS2 in MM was verified (59). Another fatty acid metabolism gene, fatty acid elongase 6 (ELOVL6), was recently shown to regulate PI resistance in MM (80). We have found that the ACSL and FABP (fatty acid binding proteins) families of are other, novel potential targets in MM (81)(82)(83).…”
Section: Lipid Mediators and Metabolism-related Enzymesmentioning
confidence: 88%
“…BZ exerts its anti-tumor effect through ER stress caused by the protein accumulation ( 53 ), because the ER is the site of lipid synthesis, and BZ also causes lipid accumulation ( 45 ). In BZ-resistant MM, it was found that the expression of SREBP1 and its downstream target FA elongase ELOVL6 are reduced, resulting in inhibiting lipid synthesis, thereby reducing the accumulation on the ER and ultimately causing BZ-resistance ( 54 ). In addition to CD36 mediating cellular uptake of FAs, FATP also mediates cellular uptake of FAs.…”
Section: Fa Metabolism In Hematological Malignanciesmentioning
confidence: 99%